PERAN FUNGSI MANAJEMEN KURIKULUM PADA SISTEM PEMBELAJARAN DARING DI MADRASAH ALIYAH AL AMIRIYYAH BLOKAGUNG - M.Imam Khaudli; Faya Aniqotur Rikza (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
In connection with the Covid-19 virus that hit, the current state of education is arguably ineffective because the learning system has changed to online. The purpose of this study was to determine the planning, implementation and evaluation of the online learning system at Madrasah Aliyah Al Amiriyyah. This research method uses descriptive qualitative. Collecting data through interviews, observation and documentation. There are three research subjects, namely the head of the Madrasah, WKM. curriculum, and one of the teachers of MA Al Amiriyyah Blokagung Tegalsari Banyuwangi. Data analysis used the theory of Miles & Huberman, namely data reduction, data presentation and conclusion drawing. The data validity technique uses triangulation. The results of the research: the planning, implementation and evaluation of the online learning system at MA Al Amiriyyah is still less effective because with the Covid-19 virus that hit, the learning system is different from before. The conclusion is that the planning, implementation, and evaluation of the online learning system at MA Al Amiriyyah is still not effective because the learning system is still unfamiliar and also different from the previous learning system.